V binokl' vidno li perspektiva : gde bude griva posle vzryva?... - Kukryniksy (Плакат СССР (Plakat), 1981)
Cartoon parody of lion representing Britain and the Pound in the sea, clinging to an island full of nuclear missiles that say 'USA'; military general and politician watch in satisfaction with binoculars Original title: В бинокль видно ли перспектива : где буде грива после взрыва?... PO-1711